2017
DOI: 10.1007/s00382-017-3609-x
|View full text |Cite
|
Sign up to set email alerts
|

Rain-on-snow events over North America based on two Canadian regional climate models

Abstract: take into consideration ROS events in water resources management adaptation strategies for future climate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(61 citation statements)
references
References 42 publications
2
44
0
Order By: Relevance
“…Here we present a comprehensive analysis of how the surface water balance responds to atmospheric forcing under AR and non‐AR conditions. Consistent with previous studies, we found that the ROS process can heavily modulate the snowpack response (Il Jeong & Sushama, ; McCabe et al, ; Musselman et al, ). Also, we quantitatively attribute the ROS effect on snowpack and runoff to surface air temperature (on average 3.49 mm/day of snow ablation) and radiation (0.97 mm/day of snow ablation) associated with ARs.…”
Section: Discussionsupporting
confidence: 92%
“…Here we present a comprehensive analysis of how the surface water balance responds to atmospheric forcing under AR and non‐AR conditions. Consistent with previous studies, we found that the ROS process can heavily modulate the snowpack response (Il Jeong & Sushama, ; McCabe et al, ; Musselman et al, ). Also, we quantitatively attribute the ROS effect on snowpack and runoff to surface air temperature (on average 3.49 mm/day of snow ablation) and radiation (0.97 mm/day of snow ablation) associated with ARs.…”
Section: Discussionsupporting
confidence: 92%
“…The Arctic is warming at twice the rate of lower latitudes and is predicted to experience elevated levels of precipitation with a higher proportion falling as rain (Olsen et al 2011, Bintanja and Selten 2014, Bring et al 2016, Vihma et al 2016. As a consequence, the snow-covered season is shortening, spring conditions are becoming more variable, and rain-on-snow events are increasing in frequency (Putkonen et al 2009, Jeong and Sushama 2017, Langlois et al 2017, Mallory and Boyce 2017. These changes in temperature and hydrology are transforming northern ecosystems, with profound implications for wildlife that are not well understood , 2011b, Chapin et al 2004, Post et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In general, there exist strong regional differences in future projections of RoS occurrence, as such changes depend on both the air temperature and associated precipitation phase (rain or snowfall) as well as the areal extent and thickness of the snowpack: In midlatitude and lowland regions, the frequency of RoS events is expected to decrease due to snowpack declines. By contrast, RoS frequency is expected to increase in high latitude and mountainous regions due to a shift from snowfall to rain but persistent seasonal snow cover (Freudiger et al, ; Jeong & Sushama, ; McCabe et al, ; Musselman et al, ; Surfleet & Tullos, ; Ye et al, ). Furthermore, projected changes in RoS frequencies are depending on the investigated climate scenario and time horizon (Beniston & Stoffel, ; Morán‐Tejeda et al, ) and might differ for different seasons (Jeong & Sushama, ).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, RoS frequency is expected to increase in high latitude and mountainous regions due to a shift from snowfall to rain but persistent seasonal snow cover (Freudiger et al, ; Jeong & Sushama, ; McCabe et al, ; Musselman et al, ; Surfleet & Tullos, ; Ye et al, ). Furthermore, projected changes in RoS frequencies are depending on the investigated climate scenario and time horizon (Beniston & Stoffel, ; Morán‐Tejeda et al, ) and might differ for different seasons (Jeong & Sushama, ). For Switzerland, Köplin et al () predict a diversification of flood types in the wintertime as well as an increase of RoS floods in the future.…”
Section: Introductionmentioning
confidence: 99%